Practice, Skill Mix, and Education: The Evolving Role of Pharmacy Technicians in Great Britain - Melanie Boughen; Tess Fenn (MDPI AG, 2020)
Pharmacy technicians’ roles are rapidly evolving in Great Britain (GB) as they undertake more extended activities with increased autonomy across the different pharmacy sectors. This paper compares the GB pharmacy regulator initial education and training standards recently introduced (2017) with the qualifications currently used in practice and discusses whether future qualifications will be ‘fit for purpose’. In this context, knowledge, skills, and competence are reviewed to assess whether they will meet the expectations and underpin the evolving pharmacy technician role as integral to healthcare provision. Based on drivers, policy change, and the changing GB healthcare landscape, effectiveness of skill mix is analysed to establish whether this is being optimised to support person-centred pharmacy in response to the challenges and pressures faced within the NHS. On this basis and given there is a limited evidence base, this review has highlighted a need for larger scale research to reassure the pharmacy and wider healthcare professions, and the public, that the evolving pharmacy technician role presents no increased risk to patient safety and contributes significantly to releasing pharmacists time for person-centred clinical activities.